89.7k views
5 votes
If 3(2x) - 4(3x) + 3 = 0. Find the possible values of x

pls help​

User VelLes
by
4.8k points

1 Answer

4 votes

Answer: x=1/2=0.5

Explanation:

Given

3(2x) - 4(3x) + 3= 0

Expand parenthesis

6x - 12x + 3 = 0

Combine like terms

-6x + 3 = 0

Subtract 3 on both sides

-6x + 3 - 3 = 0 - 3

-6x = -3

Divide -6 on both sides

-6x / -6 = -3 / -6

x = 1/2 = 0.5

Hope this helps!! :)

Please let me know if you have any questions

User TechGuy
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.